2023
DOI: 10.7759/cureus.34872
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of the Spike Protein in Neurodegenerative Diseases: A Narrative Review

Abstract: Human prion protein and prion-like protein misfolding are widely recognized as playing a causal role in many neurodegenerative diseases. Based on in vitro and in vivo experimental evidence relating to prion and prion-like disease, we extrapolate from the compelling evidence that the spike glycoprotein of SARS-CoV-2 contains extended amino acid sequences characteristic of a prion-like protein to infer its potential to cause neurodegenerative disease. We propose that vaccine-induced spike protein synthesis can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 139 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…The spike protein is not only toxic through binding of ACE-2 receptors, but it also has cytotoxic effects inside cells through interaction with cancer suppressor genes BRCA and P53 and mitochondrial damage, coagulopathies through direct contact with cellular proteins, and is neurotoxic through accumulation, with spread and reconfiguration of prion proteins into their pathologic form. The accumulation of spike protein inside cells could have toxic and apoptotic effects [ 29 ].…”
Section: Structure Of Sars-cov-2 Spike Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The spike protein is not only toxic through binding of ACE-2 receptors, but it also has cytotoxic effects inside cells through interaction with cancer suppressor genes BRCA and P53 and mitochondrial damage, coagulopathies through direct contact with cellular proteins, and is neurotoxic through accumulation, with spread and reconfiguration of prion proteins into their pathologic form. The accumulation of spike protein inside cells could have toxic and apoptotic effects [ 29 ].…”
Section: Structure Of Sars-cov-2 Spike Proteinmentioning
confidence: 99%
“…Seneff and colleagues, in an extensive narrative review of potential pathophysiological mechanisms of the spike protein in neurodegenerative diseases, describe “the spike protein’s contributions, via its prion-like properties, to neuroinflammation and neurodegenerative diseases; to clotting disorders within the vasculature; to further disease risk due to suppressed prion protein regulation in the context of widely prevalent insulin resistance” and “explain why these prion-like characteristics are more relevant to vaccine-related mRNA-induced spike proteins than natural infection with SARS-CoV-2” [ 29 ] (abstract p.1). Key findings they reviewed included: Spike-induced endotheliitis disturbs the blood-brain barrier and exacerbates Alzheimer’s disease via the interaction of the spike protein with amyloid β or hyperphosphorylated tau [ 164 ].…”
Section: Evidence Of ‘Spikeopathy’—spike Protein Pathogenicitymentioning
confidence: 99%
“…Although it is unknown at present whether secondary damage is caused by transfusion of blood products derived from genetic vaccine recipients, it is necessary for medical institutions and administrative organizations to respond and investigate cooperatively, keeping various possibilities in mind, because mechanisms such as the toxicity of the spike protein itself and the effects of LNPs and modified mRNA on the immune response have not been fully elucidated and are still under study. It should be emphasized that a significant proportion of the COVID-19 PVS in mRNA vaccine recipients is due to toxic spike proteins, and the inclusion of structures in the receptor-binding domain within these proteins that may induce prion disease is particularly alarming, as Seneff et al and Perez et al have warned [50,[90][91][92][93][94][95][96]. Furthermore, it has been shown that prion similarity in the receptor-binding domain exists not only in the spike protein of the Wuhan strain, which is still used as an antigen in genetic vaccines, but also in the spike protein of variants of SARS-CoV-2, such as the Delta strain, with the exception of the Omicron strain [93,97].…”
Section: Overview Of Cases Of Blood Abnormalities After Genetic Vacci...mentioning
confidence: 99%
“…In this section, we provide specific proposals on how to respond to these circumstances. Because blood contamination affects so many areas of health care, it is especially important to anticipate the worst [95,96,[108][109][110] and to plan and act from the start to ensure that there are no lapses or omissions.…”
Section: Specific Proposals For Blood Sampling and Blood Products Fro...mentioning
confidence: 99%
“…Some authors have hypothesized a possible neurodegenerative mechanism linked to the spike protein which would acquire prion-like properties. In particular, according to these authors, following vaccination with mRNA vaccines for Sars-CoV-2, the spike protein could be produced in excessive quantities by cells and interact with other prion-like proteins leading to the formation of aggregates ( 127 ). It could be hypothesized that this mechanism also occurs following viral infection by Sars-Cov-2 and could be connected to neurodegeneration.…”
Section: Neuroinflammation Induced By Sars-cov-2: a Link To Neurodege...mentioning
confidence: 99%